Socio-Demographic Variations on Age-Sex Mortality in Namibia: An Analysis of the 2016 Civil Registration and Vital Statistics Data - Shipanga, Immanuel; Oyedele, Opeoluwa; Matengu, Tarcy C. (Namibian Journal for Research, Science and Technology, 2022)
Mortality studies are important for the effectiveness of subsystem of health services in a country. Before the Coronavirus pandemic outbreak, there has been a gradual decline in the global mortality indicators, which can be linked to the improving economic development and social wellbeing of the global population, especially, in developing regions such as East Asia and the Pacific, Latin America and the Caribbean, Eastern Europe and the Middle East. This decline in mortality and the high fertility in developing countries are the contributing factors to the increase on global population. Apart from the aggregated frequencies of deaths and crude death rates reported in population census reports, little to no attention has been paid to detailed inference mortality analysis with respect to the age-sex variation perspective in Namibia. Thus, this paper used the negative binomial regression modelling technique to perform an inference mortality analysis across all ages and both sexes in the country as well as across regions and marital status using the 2016 Civil Registration Vital systems data from the Ministry of Home Affairs and Immigration. Results showed that there was a significant relationship between mortality and theindividuals' age, sex, marital status and region. In addition, Oshana, Kavango East, Khomas, Hardap and Omaheke regions had high mortality rates, while infants and elderly individuals had a high probability of dying. Furthermore, the study revealed that individuals who were single and aged 15-59 and 5-14 years had less expected death count. Hence, it is recommended that interventions (such as affordable and proper health care and well-being services) targeted at the (most) vulnerable age groups, marital group and regions be made a priority, in order to meet Sustainable Development Goal 3.